Designing Versailles: landscapes and the perspectival peace: Dedicated to the memory of Frederick Arthur Farrell (29 November 1882 – 22 April 1935). Issue 1 (23rd October 2020) - O'Donnell, Thérèse
Abstract: This article analyses the 1919 peace treaty's signing at Versailles, and what the magnificent staging signalled about the peace terms, notably regarding power and emerging notions of self-determination. In 1919, international society appeared to be on the threshold of a new era. However, a dissonance emerged between the peacemakers' proclamations and the operationalisation of new principles of openness and emancipation. Certain royal houses and empires may have vanished but the remaining power-holders were not about to relinquish their dominance. While the familiar, blunt-edged tools of brazen colonialism were no longer available, some finer instruments and skilled professional expertise would finesse the details of an unequal hegemonic future. In all senses, this was a design project and in acknowledgement of Versailles's backdrop and the peacemakers' cartographic approach, landscape architecture's specialist principles offer a lens for comprehending and critiquing the legal-political practices of Versailles 1919.